2018
DOI: 10.3906/vet-1806-52
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green tea waste extract on ruminal degradability and intestinal digestibility of barley grain

Abstract: This study was conducted to investigate the effects of different levels of green tea waste extract (GE) on ruminal degradability and intestinal digestibility of dry matter (DM), crude protein (CP), and starch of barley grain. Therefore, barley grain was treated with 0 as control, and 5%, 10%, 15%, and 20% of GE. The potential of DM degradability (a + b) of barley grain treated with 15% and 20% of GE was significantly lower compared to other treatments (Linear [L] P < 0.05). The lowest (a + b) fraction of CP de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, inhibitory effects on protein proteolysis often occur, and in some conditions, the polymer–tannin bond fails to be absorbed as rumen undegradable protein (RUP) in the intestine. Nasehi et al [ 57 ] reported that tannin reduced the ruminal degradability of plant proteins and enhanced the intestinal bioavailability of amino acids in ruminants. By contrast, our evidence showed that the presence of tannin extract negatively influenced rumen protein degradability and total tract apparent digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibitory effects on protein proteolysis often occur, and in some conditions, the polymer–tannin bond fails to be absorbed as rumen undegradable protein (RUP) in the intestine. Nasehi et al [ 57 ] reported that tannin reduced the ruminal degradability of plant proteins and enhanced the intestinal bioavailability of amino acids in ruminants. By contrast, our evidence showed that the presence of tannin extract negatively influenced rumen protein degradability and total tract apparent digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Total-tract NDF digestibility (TTNDFD), calculated as ruminal NDF digestion + hindgut NDF digestion, has recently been demonstrated to be a good predictor of forage digestibility [ 26 , 27 ]. A large number of studies have been conducted to investigate the ruminal degradability, iNDF, and total-tract digestibility (TTD) of concentrate feeds [ 20 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and high-quality forages such as CSil [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], AH [ 41 , 42 , 46 , 48 , 49 , 50 ], and oat hay [ 46 , 48 ] during the last two decades. However, studies on ruminal degradability, iNDF content, intestinal digestibility (ID), and TTD of the crop straws, especially CS, RS, and WS are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the nylon bag method [30][31][32] was used to reanalyze the rumen degradation characteristics of DM, CP, ADF, and NDF. Each cow was regarded as a replicate, each forage three replicates, and each forage had two parallel replicates per cow (n = 6).…”
Section: In Situ Nutrient Degradabilitymentioning
confidence: 99%